PEMBERIAN PUPUK AB MIX PADA TANAMAN PAKCOY PUTIH (Brassica rapa L.) DENGAN SISTEM HIDROPONIK RAKIT APUNG - Muhammad Fuad Syah; Ardian; Arnis En Yulia (UIR Press, 2021)
This research aims to obtain the proper nutrient concentration and the best nutrient concentration and increase the growth and yield of pakcoy through the floating hydroponic system. The research was conducted in the Experimental Farm of the Faculty of Agriculture, University of Riau from October to November 2019. The research used a non-factorial completely randomized design (CRD), consisting of 5 treatments and 4 replications. The given treatment was the nutrient concentration of AB Mix consisting of 5 levels: AB Mix 1000 ppm, AB Mix 1200 ppm, AB Mix 1400 ppm, AB Mix 1600 ppm, and AB Mix 1800 ppm. The parameters observed were plant height, leaf number, leaf area, root volume, plant fresh weight, and worthy weight consumption. The result showed that all the given treatments did not have significant towards all parameters. The concentration of 1000 ppm is the best concentration of some else, because more efficient, economic and saves the solution uses of nutrien in concentration. Based on the results of a study that has been conducted, to gain growth and the results of white pakcoy plant are both hydroponic can usea concentration of AB Mix 1000 ppm.